Tax Compliance and Economic Growth: Empirical Investigation of Developing Economies - Sewak , Dr. Shilpa; Asbe , Dr. Chetana; Biswal , Dr. Saroj Kanta; Sandhya, V.; Sandeep , V.; Sharma, Rajeev; Garg, Avni (International Journal of Accounting and Economics Studies, 2025)
In today's world, everyone feels the impact of the tax policies set by their government, whether they realize it or not. Tax policy is a sensitive and vital topic for both the government and its citizens. When it comes to political and economic matters, few issues spark as much debate and reflection as taxation and how it's enforced. Back in the day, the role of a state or government was pretty limited, mainly focused on protecting its borders and maintaining law and order. Nowadays, however, governments have taken on a much broader role, needing to implement various development projects and welfare programs for their citizens. The responsibilities of modern governments have expanded significantly. Naturally, this means they require substantial funds and resources to support their public spending and transfer initiatives. Effective resource mobilization, particularly through a solid tax policy and its successful execution, has become essential for every government. Recently, many governments have adopted new strategies and policy measures to address this need, and it's clear that tax collections have surged in numerous countries. There's a prevailing belief among many economists and researchers that the expansion of government roles and the increase in tax revenue have led to a tax revolt, higher rates of tax evasion, a rise in the underground economy, and a backlash against welfare programs.